Leksem patchwork we współczesnej polszczyźnie - Piotrowicz, Anna; Witaszek-Samborska, Małgorzata (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
The article is devoted to the semantic evolution of the word patchwork, which has become frequent in contemporary Polish. This appropriate borrowing from English was registered in Polish lexicography for the first time in 1995. In the twenty years since then, it showed its new meanings different from the original ‘artistic handicraft technique, consisting in stitching together pieces of material of different colours and shapes’, ‘composition resulting from the use of this technique’ and ‘product formed in this manner, for example bedspread, tapestry, clothes’. Nowadays, this lexeme can refer to any term referring to a particular or abstract designatum which ‘creates a coherent whole, but consists of various elements’ and also – as a derivatives of phraseology the patchwork family – means ‘a family founded by parents, at least one of whom has had a previous unsuccessful relationship or marriage involving their common children, their children from previous relationships, and sometimes also former partners and their relatives’.